Linguistic Challenges, Translational Strategies, and Cultural Mediation in Uzbek, Kazakh, and English Literary Translation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the process of literary translation among the Uzbek, English, and Kazakh languages. It analyzes the linguistic, cultural, and stylistic obstacles that emerge when translating literary works among these three languages. Through the analysis of actual examples from prose and poetry, the article emphasizes the methods translators employ to maintain meaning, style, and cultural units while engaging new audiences.